Systematic review of structural and immunological features of mollusk toll-like receptors in aquaculture context - Li, Hongyu; Li, Xianwei; Zhu, Yunhuan; Xu, Jialu; Zhao, Qingzhi; Chen, Xintong; Zhang, Yijie; Zhao, Ling; Chen, Yutong; Weng, Ruiqi; Chen, Keda (Frontiers in Immunology, 2025)
IntroductionToll-like receptors (TLRs) are transmembrane proteins essential for innate immunity. While vertebrate TLRs have been well studied, knowledge of their distribution, structure, and function in mollusks remains limited, despite their importance in pathogen defense and environmental adaptation.MethodsThis review synthesizes current findings on molluscan TLRs, focusing on their structural features, tissue-specific expression, immune functions, and responses to environmental pollutants.ResultsMolluscan TLRs exhibit broad distribution and notable structural diversity. Their expression is tissue-dependent and can be modulated by pathogenic and environmental stressors. Although divergent from vertebrate TLRs in sequence homology, they share functional parallels in innate immune signaling. Evidence also indicates that pollutant exposure can alter TLR expression, influencing immune capacity.DiscussionMolluscan TLRs provide insight into species-specific immune strategies and hold potential for applications in disease management and ecological monitoring. Continued research will enhance understanding of innate immunity and support progress in comparative immunology.